Characteristics Nanoparticle of Propolis Ethanol Extracts with Variations of Chitosan-Sodium Alginat - Santi Sinala1,4 , Marianti A.Manggau2 , Sartini2 , Rudy Hartono3,4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nanoencapsulation technology has many advantages, which include important roles in drug delivery and protection of bioactive components that have perishable stability, one of which is polyphenol compounds. Propolis which contains high levels of polyphenol compounds has been used as an antioxidant for various diseases. By making nanoparticles from propolis, it can maintain the stability of polyphenol compounds from propolis and increase the effect of treatment through optimal delivery. Nanoformulations containing ethanol extract of propolis were absorbed by chitosan-sodium alginate using an ionotropic pre-gelation method. Optimization is carried out at various concentrations of chitosan, namely 0.05%; 0.075%; 0.1% and 0.125% , with the use of the same sodium alginate concentration which is 0.0063%. Testing of nanoparticle characteristics includes particle size and morphology and adsorption efficiency (EE) consisting of total flavonoid and total polyphenol values. The increase in chitosan polymer is directly proportional to the increase in particle size, but does not occur in the absorption efficiency value. The 0.05% chitosan formula showed the absorption of polyphenol compounds at 99.41% with particle sizes of 259.12 nm